Respons Tanaman Sawi Hijau (Brassica juncea L.) Pada Pemberian Pupuk Organik Cair Eceng Gondok (Eichhornia crassipes) Dan Pupuk Anorganik - Manopo, Debora Novia; Tumewu, Pemmy; Rantung, Meity (Sam Ratulangi University, 2024)
This study aims to determinate the effect of the interaction between water hyacinth (Eichhornia crassipes) liquid organic fertilizer on mustard greens (Brassica juncea) fertilizer that affects the yield of mustard greens and determine the dose of inorganic fertilizer that affects crop yield mustard greens. This research was conducted in the village of Motoling, Kec. Motoling, south Minahasa Regency, North Sulawesi. The design of this study used a factorial randomized block design (RBD) with factor I, namely the dose of water hyacinth liquid organic fertilizer, and factor II, namely the dose of inorganic fertilizer. The variables observed were: plant height, number of leaves, leaf lenght, leaf width and wet weight. The results showed that the interaction between water hyacinth liquid organic fertilizer and inorganic fertilizers had an effect on the fresh weight of mustard green plants and had no effect on plant height, number of leaves, leaf length dan leaf width of mustard green plants.